Analytical model for evaluating lateral force capacity of precast concrete-filled steel tube column. (15th December 2022) - Zhang, Kaidi; Jia, Junfeng; Li, Ning; Zhao, Jianyu; Bai, Yulei
Highlights: A non-iterative analytical model was derived to evaluate the lateral force capacity of precast columns. The neutral axis depths of precast columns with concrete section confined by steel tube were developed by nonlinear regression analysis. The influences of the various parameters on the lateral force capacity of precast columns were investigated. Abstract: Precast segmental columns have been frequently applied in regions of low seismicity due to rapid construction, high quality, and low downtime. Their lateral force–displacement curves were always calculated using iterative models in former studies, which could be time-consuming and arduous. Whereas, a non-iterative model can greatly improve computational efficiency and is preferred by designers. In this study, a non-iterative simplified analytical model was firstly proposed considering different neutral axis depths of the rocking interface. The neutral axis depth approached a constant value during lateral loading according to the results of the former tests and numerical studies. Then, a quasi-static test and finite element model of a precast segmental concrete-filled steel tube (PS-CFST) column were conducted to verify the proposed analytical model. Based on the finite element model, a nonlinear regression equation was set up to predict the constant neutral axis depth of the PS-CFST column according to the simulation results of 48 cases. Finally, the influence of the initial prestressing force, area of the prestressed tendons and gravity load on the lateral force capacity of the PS-CFST column were investigated. It was concluded that the constant value of neutral axis depth was positively related to axial ratio and diameter-thickness ratio, and negatively related to yield strength of steel tube of PS-CFST columns. The analytical model without iteration proposed in this study was appropriate to predict lateral force capacity of post-tensioned precast segmental columns, and it had a favorable agreement with testing and numerical results. Furthermore, the precast column with the lower gravity load and the higher reinforcement ratio of prestressed tendons would result in the larger post-yield stiffness.